PERAN PENYIDIK BADAN NARKOTIKA NASIONAL SUMATERA UTARA DALAM PEMBERANTASAN PEREDARAN GELAP NARKOTIKA DI KOTA MEDAN - Partomuan Partomuan Kristina Simbolon; Nurmaya Nurmaya R A Simanjuntak (Judge : Jurnal Hukum, 2025)
This study examines the function of investigators from the National Narcotics Agency of North Sumatra Province (BNNP) in combating illicit narcotics trafficking in Medan City, a role mandated by Law No. 35 of 2009 concerning Narcotics. The research concentrates on the operational execution of investigations, inter-agency coordination with other law enforcement bodies, and eradication activities achieved through public cooperation. The analysis indicates that BNNP investigators act as a pivotal entity, integrating technology-based intelligence with community participation to dismantle narcotics syndicates. Nevertheless, the overall efficacy of these investigations is impeded by both internal and external constraints. Consequently, the researcher recommends strengthening investigator capacity via intelligence training, allocating greater resources, and implementing systematic community empowerment programs to enhance public reporting and involvement. Executing these recommendations is expected to elevate the investigation success ratio and the effectiveness of counter-narcotics efforts in Medan City.